PELECEHAN SEKSUAL TENAGA KERJA WANITA INDONESIA DALAM HUBUNGAN INDUSTRI - Meci Nilam Sari (JIANA ( Jurnal Ilmu Administrasi Negara ), 2017)
Abstract: Sexual Harassment Labor Women Indonesia in Industrial Relations. The purposeof this study is to investigate the sexual harassment of women workers Indonesia and how theprevention of sexual harassment in industrial relations. This research in the form of library research,which comes from secondary data sources, documents and relevant theory. Analysis ofdata using qualitative descriptive study findings based on the data source literature and secondarydata. For sharpening the analysis is then conducted interviews with sources in question are experiencingsexual harassment. The results show the high level of harassment for female workersin the protection of working hours, the menstrual period, pregnancy and lactation facility has notbeen implemented properly in accordance with the legislation in force.